2018
DOI: 10.4028/www.scientific.net/msf.925.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si and Ni Addition on Graphite Morphology in Heavy-Section Spheroidal Graphite Iron Parts

Abstract: Abstract. Metallographic analysis is applied to the study of the chunky graphite morphology in heavy-section castings of spheroidal graphite cast irons. Three castings with different Si and Ni contents were prepared. Three positions in casting from the edge to the centre, with different cooling rates, were chosen for microstructure observation. The effect of the Si and Ni content on the graphite morphology and mechanical properties of heavy-section spheroidal graphite cast iron parts was investigated. Cerium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…No detailed micrographs of chunky graphite are reported in Reference 18, even if the presence of chunky graphite has been widely reported for heavy section products. 9,10,19,20 In Table 3, also in 4.5 wt% HSSDI some graphite degeneracy was present with considerable nodularity decrease, and some chunky graphite is also reported in Figure 4. So, even if no correlation as reported in References 19 and 20 between the unusual plastic behavior and chunky graphite was possible, there was an evident connection between unusual plastic behavior and graphite degeneracy that is known to be detrimental for tensile mechanical properties.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…No detailed micrographs of chunky graphite are reported in Reference 18, even if the presence of chunky graphite has been widely reported for heavy section products. 9,10,19,20 In Table 3, also in 4.5 wt% HSSDI some graphite degeneracy was present with considerable nodularity decrease, and some chunky graphite is also reported in Figure 4. So, even if no correlation as reported in References 19 and 20 between the unusual plastic behavior and chunky graphite was possible, there was an evident connection between unusual plastic behavior and graphite degeneracy that is known to be detrimental for tensile mechanical properties.…”
Section: Discussionmentioning
confidence: 84%
“…In DIs produced through heavy sections where the solidification rates are very slow, the nodule count decreases and nodule size increases, while graphite degenerates causing the decrease in nodularity and even the possible appearance of chunky graphite. 9,10 All of this leads to decreasing and scattering mechanical properties. 11,12 So in heavy sections, the sizes and the density of defects are expected to affect significantly the strain hardening behavior and the quality assessment procedure might need some corrections.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies reveal different quantitative results on a maximum tolerable Si content (1.8-2.4%) depending on the solidification time (wall thickness) and the contents of trace elements (also called tramp or accompanying elements). 6,9,13,25,33,37,41,42,49 With the recently standardized grades of solid solutionstrengthened ferritic SGI, the Si content is a matter of special interest. [50][51][52] With these SGI grades, Si is limited to approximately 4.2% 50 since above this limit Fe-Si superstructures gain detrimental influence on the mechanical properties [53][54][55] and chunky graphite appears.…”
Section: Effect Of Chemical Elementsmentioning
confidence: 99%
“…74 chunky graphite. 1,3,8,9,14,20,47,49,51,66,73,82,[91][92][93][101][102][103] Consequently, premature failure of the whole chunky graphite affected region in a component may arise, 1,8,47,82 and cleavage fracture in areas otherwise consisting exclusively of ferrite and graphite nodules is promoted. 82,91,92,102,103 The fundamental correlations between chunky graphite and strength as well as ductility demonstrated for low Si ferritic SGI have been confirmed in Reference 52 for silicon contents up to 4.0%.…”
Section: Strength and Ductilitymentioning
confidence: 99%
“…They decrease the quantity of carbon soluble in the austenite and thus increase the quantity of free carbide in the iron at a given carbon content. Recent research works [13,15,[19][20][21][22][23][24] have shown that, Si, Mn, Ni, Mo, V, Cu, Ti, Nb, W, Sn… are the typical alloying elements used to control ferrite and pearlite contents and increases mechanical properties in ductile iron as-cast grades. Mn and Cu are used to promote pearlite, Si is used to promote ferrite and to strengthen it.…”
Section: Introductionmentioning
confidence: 99%